2021
DOI: 10.1111/eje.12680
|View full text |Cite
|
Sign up to set email alerts
|

Digital anatomy table in teaching‐learning process of the temporomandibular joint anatomy

Abstract: Introduction The use of teaching resources and digital objects has gradually been incorporated into dental schools. This study aimed to evaluate the digital anatomy table in teaching‐learning process of the temporomandibular joint (TMJ) anatomy and the student's perception regarding this resource. Materials and Methods A cross‐sectional study was conducted on 41 undergraduate dental students. Knowledge assessment tests were applied at different time intervals: before and after the TMJ theoretical class, after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…A cross-sectional study on first-year medical students of Imam Mohammad Ibn Saud Islamic University reported that the Anatomage with plastinated specimens is more effective compared to the cadaveric dissection in anatomy learning, as the students can understand the anatomical location and the surrounding area when using Anatomage as compared to cadaver dissection [ 21 ]. da Silveira et al noticed higher median scores of teaching strategy with Anatomage in students' perception of temporomandibular joint anatomy [ 34 ]. Similarly, Kažoka et al noticed that the Anatomage table improved visualization and memorization of the different anatomical organs [ 10 ].…”
Section: Reviewmentioning
confidence: 99%
“…A cross-sectional study on first-year medical students of Imam Mohammad Ibn Saud Islamic University reported that the Anatomage with plastinated specimens is more effective compared to the cadaveric dissection in anatomy learning, as the students can understand the anatomical location and the surrounding area when using Anatomage as compared to cadaver dissection [ 21 ]. da Silveira et al noticed higher median scores of teaching strategy with Anatomage in students' perception of temporomandibular joint anatomy [ 34 ]. Similarly, Kažoka et al noticed that the Anatomage table improved visualization and memorization of the different anatomical organs [ 10 ].…”
Section: Reviewmentioning
confidence: 99%
“…7,8 The literature has highlighted relevant results from the use of ICTs as auxiliary tools in the formation of knowledge and support in the learning of dentistry. 3,9 ICTs have also been shown to be adequate tools to assist in the diagnosis and therapeutic decision of traumatic dental emergencies. 6,8 This may represent an even greater strength of the approach, as traumatic injuries are well-recognised as a public health issue with an immediate need for proper management.…”
Section: Introductionmentioning
confidence: 99%
“…The use of information and communication technology (ICT) has been shown to be effective in the teaching‐learning process. It incorporates digital innovations that bring knowledge and audiovisual information to teaching, 1 modifying students' interaction with knowledge and making the educational setting more attractive and motivating 2,3 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations